2020
DOI: 10.1093/biolre/ioaa191
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity alters placental lysophosphatidylcholines, lipid storage, and the expression of genes associated with lipid metabolism

Abstract: Dyslipidemia is a characteristic of maternal obesity and previous studies have demonstrated abnormalities in fatty acid oxidation and storage in term placentas. However, there is little information about the effect of pre-pregnancy obesity on placental lipid metabolism during early pregnancy. The objective of this study was to determine the relationship between lipid profiles and markers of metabolism in placentas from obese and lean dams at mid-gestation. Mice were fed a western (WD) or normal (ND) diet and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In a human study, Yamazaki et al [ 98 ] showed that even placental pathologies due to maternal (gestational hypertension or preeclampsia) or fetal (small for gestational age) diseases may disturb the lipid composition in the terminal and stem villi at delivery. In a mouse study, a US research group [ 99 ] showed that maternal diet and obesity strongly influence the lipid composition of the placenta of mice on gestational day 12.5: there was a 2.5 to 6-fold increase in PC36:1, PC38:3, LPC16:1, LPC18:1, and LPC20:1 in the decidua of the obese group following a Western diet compared to lean mice on a normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…In a human study, Yamazaki et al [ 98 ] showed that even placental pathologies due to maternal (gestational hypertension or preeclampsia) or fetal (small for gestational age) diseases may disturb the lipid composition in the terminal and stem villi at delivery. In a mouse study, a US research group [ 99 ] showed that maternal diet and obesity strongly influence the lipid composition of the placenta of mice on gestational day 12.5: there was a 2.5 to 6-fold increase in PC36:1, PC38:3, LPC16:1, LPC18:1, and LPC20:1 in the decidua of the obese group following a Western diet compared to lean mice on a normal diet.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that maternal obesity alters the placental architecture and negatively impacts fetal growth and development [7][8][9][10]. Placental lipid accumulation is also dramatically increased in obese mothers as compared to lean mothers [11]. A recent study obtained obese placenta from the first trimester of pregnancy and showed increased lipid accumulation and altered expression of major lipid metabolic genes in the placenta [9].…”
Section: Introductionmentioning
confidence: 99%
“…These omic-based readouts have demonstrated the presence of altered neutral and polar lipid profiles (highlighted by changes in underlying fatty acid (FA) composition) in the placentae from obese and GDM pregnancies [ 38 , 39 , 40 , 41 , 42 ]. In addition, pre-clinical mouse models of diet-induced maternal pre-gestational obesity have also described metabolomic and transcriptomic markers associated with altered placental lipid composition and metabolism [ 43 , 44 ]. Overall, the current literature has highlighted that abnormal lipid processing occurs in the obese and diabetic placenta.…”
Section: Introductionmentioning
confidence: 99%